Deployment of low-level ozone-enrichment for the preservation of chilled fresh produce - Tzortzakis, Nikos G.; Singleton, Ian; Barnes, Jeremy D. (My University, 2007)
Tomatoes, strawberries, table grapes and plums were inoculated with Botrytis cinerea (grey mould), transferred to chilled storage (13 °C) and exposed to 'clean air' or low-level ozone-enrichment (0.1 μmol mol-1). Ozone-enrichment resulted in a substantial decline in spore production as well as visible lesion development in all treated fruit. Exposure-response studies performed specifically on tomato fruit (exposed to concentrations ranging between 0.005 and 5.0 μmol mol-1 ozone) revealed lesion development and spore production/viability to be markedly reduced in produce exposed to ozone prior to, or following, infection with B. cinerea; higher concentrations/duration of exposure yielding greater reductions in lesion development and spore production/viability. Impacts on Botrytis colonies grown on Potato Dextrose Agar (PDA) for 5-6 days at 13 °C and 95% relative humidity (RH) revealed less effects than studies on fruit inoculated with the pathogen in vivo. Taken as a whole, the results imply that ozone-induced suppression of pathogen development is due, to some extent, to impacts on fruit-pathogen interactions. This work suggests that ozone may constitute a desirable and effective residue-free alternative to traditional postharvest fungicide practices. Data presented illustrate that optimal ozone treatment regimes are likely to be commodity-specific and require detailed investigation before such practices can be contemplated commercially. © 2006 Elsevier B.V. All rights reserved.
Keywords: Botrytis cinerea; Fresh produce; Microbial spoliage; Modified atmosphere storage; Ozone; Tomato